2014
DOI: 10.1128/aem.04034-13
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization Has a Stronger Effect on Soil Nitrogen-Fixing Bacterial Communities than Elevated Atmospheric CO 2

Abstract: c Biological nitrogen fixation is the primary supply of N to most ecosystems, yet there is considerable uncertainty about how Nfixing bacteria will respond to global change factors such as increasing atmospheric CO 2 and N deposition. Using the nifH gene as a molecular marker, we studied how the community structure of N-fixing soil bacteria from temperate pine, aspen, and sweet gum stands and a brackish tidal marsh responded to multiyear elevated CO 2 conditions. We also examined how N availability, specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 52 publications
6
57
1
3
Order By: Relevance
“…Different colors refer to different phyla ecosystem, the observation was consistent with several recent studies [7,53]. For example, Berthrong et al found relatively small effects of CO 2 treatment on N-fixing bacterial community in the four long-term eCO 2 experimental sites they investigated, and no consistent differences were observed for nifH diversity between aCO 2 and eCO 2 soils [7]. Notably, although only two OTUs were found for the genus Frankia, they were about eightfold more abundant than in aCO 2 , which is also consistent with a previous study that the activity of Frankia species increased with infertile soil in response to eCO 2 [54].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Different colors refer to different phyla ecosystem, the observation was consistent with several recent studies [7,53]. For example, Berthrong et al found relatively small effects of CO 2 treatment on N-fixing bacterial community in the four long-term eCO 2 experimental sites they investigated, and no consistent differences were observed for nifH diversity between aCO 2 and eCO 2 soils [7]. Notably, although only two OTUs were found for the genus Frankia, they were about eightfold more abundant than in aCO 2 , which is also consistent with a previous study that the activity of Frankia species increased with infertile soil in response to eCO 2 [54].…”
Section: Discussionsupporting
confidence: 93%
“…16S OTUs were represented by circular shape. Different colors refer to different phyla ecosystem, the observation was consistent with several recent studies [7,53]. For example, Berthrong et al found relatively small effects of CO 2 treatment on N-fixing bacterial community in the four long-term eCO 2 experimental sites they investigated, and no consistent differences were observed for nifH diversity between aCO 2 and eCO 2 soils [7].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations